Evaluation of abamectin effect on some biochemical constituents and histological alterations in Asian sea bass (Lates calcarifer) - Thanomsit, Chutima (Asian Health, Science and Technology Reports, 2016)
The aim of this study was to evaluate the effect of abamectin at the concentrations of 5, 10 and 15 µg/L for 24, 48 72 and 96 h on Asian sea bass (Lates calcarifer, Bloch). The results indicated that plasma electrolyte (Na+ and Cl-) in the exposed Asian sea bass significantly increased with an increasing of time after exposed to 5 µg/L of abamectin, at the same time, protein content in gill and liver significantly decreased. For histological alteration, we found that the alteration levels in gill, kidney and liver were increased with increasing exposure time. The histological alteration in gills was epithelial lifting and partial fusion of lamellae. It was found that the degradation of tubular, melanomacrophage aggregate, glomerulus deformed and necrosis of tubular cell in the kidney of exposed fish. Moreover, the results revealed vacuolation, blood congestion, and enlargement of sinusoid and necrosis of hepatocyte in the liver of the exposed fish.